Análisis de los costos de producción de la planta de tratamiento de agua potable de Trujillo, Proyecto Especial CHAVIMOCHIC - 2020 - Luján Flores, Grecia Nicolle (2021)
The problem of this study was: In what way do production costs reflect the productive efficiency of the Trujillo, PECH drinking water treatment plant during 2020? and the hypothesis was formulated: The production costs reflect the productive inefficiency of the drinking water treatment plant of Trujillo, PECH during the year 2020. Research with a quantitative approach, applied type, non-experimental descriptive cross-sectional design, population and sample is constituted for the data recorded for each month during the year 2020 on the production and production costs of the drinking water treatment plant; the deductive method was used; The technique used was documentary analysis and the instrument was the documentary analysis record. The results found in the Trujillo del PECH Drinking Water Treatment Plant were: 32,269,072 m3 of treated water was produced, with a raw water use of 35,611,910 m3. Income from the sale of drinking water production to the SEDALIB S.A. Company, amounted to S / 7,341,213.00 soles. Total, production costs in the PTAPT amounted to S / 6,700,198.31 soles, obtained from: the cost of raw water (direct raw material) was S / 3,810,474.37 soles, the cost of reagents (indirect raw material) was S / 1,125,393.94. The cost of spare parts, equipment and tools (indirect raw material) was S / 327,000.00 soles. Labor costs amounted to S / 1,306,500.00 soles. Indirect manufacturing costs were S / 130,830.00 soles. It is concluded that productivity increased when a lower amount of inputs used, which means lower costs, generated the same or greater production, that is, productivity in the months of 2020 was very low, except for the months of April and May. In the month of April, it is explained that for every sun (s / 1.00) that was invested, one sun twenty (s / 1.20) was obtained. We can specify that the costs of the factors used in the months of April and May are regularly efficient. The factor costs used in the months of January, February, March, June and July are weakly efficient. In contrast to the costs of the factors used in the months: August, September, November and December, they are not efficient.